Gendered Differences in Nutritional status of Fish Consuming Households in Kerala, India - Jeyya Jeyanthi, Pe.; Sankar, T.V.; Anandan, R.; Mathew, Suseela; Gopal, Nikita (Fishery Technology, 2020)
Malnutrition, the deficiencies, excesses or imbalances in a person’s intake of energy and/or nutrients, covers two groups of conditions viz., ‘under nutrition’ and ‘over nutrition’. Malnutrition impacts globally across households, communities and countries with 0.46 and 1.90 billion adults being in under and over nutrition conditions, respectively. The level of malnutrition is generally higher among women and children. A cross-sectional study was undertaken to assess the nutritional status in Vadi and Kottarakkara villages, Kollam District, Kerala, India with emphasis on gender differences in the nutritional status of fish consuming households. The Body Mass Index (BMI) of children, adolescents and adults was calculated as per World Health Organisation (WHO) classification. In coastal village, 55% of boys and girls were of normal weight, and in non-coastal village 40.74% boys and 60.47% girls were normal weight. BMI of adolescents showed that 55.17% of boys and 63.64% girls were underweight. Majority of adults (64.71%) showed normal weight which included 56% women and 73% men. There is no prominent gender difference in nutritional status and demography, literacy and job were found to influence the nutritional status of fishers.